(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
Phosphorus solubilizing bacteria (PSB) are a type of plant growth-promoting rhizobacteria which has the ability to convert insoluble phosphate into plant available forms. They are used as biofertilizers to restore soil health and fertility. In the present investigation, isolation, characterization and optimization of phosphate solubilizing activity of these microbes at different pH, temperature and carbon source was carried out. Eight phosphorus solubilizing rhizospheric bacteria (PSRB) isolates isolates were recovered from different farms in six local government from maize rhizosphere using the spread plate method on Pikovskaya agar. Amongst these eight isolates, five were recovered from Lafia local government while three were recovered from Kokona local government with the development of a prominent halozone. All isolates were morphologically characterised, amplified, and sequenced for taxonomic identification using 16S primers. The results indicated they belong to member of the genus Acinetobacter, Ochrobactrum, Brucella, Curtobacterium, Leifsonia and Microbacterium respectively. These strains when grown at different conditions of external carbon sources, temperature and pH showed highest phosphorus solubilizations of 326.23 µg/ml ± 0.21 at 30 °C, 325.50µg/ml ± 1.13 at a pH of 7 and 320.30µg/ml ± 0.36 with glucose as carbon source. The results from these findings could indicate the use of these isolate as trial biofertilizers on the field which will help improve crop yield and enhance plant growth promotion